Nimesulide induced Stevens- Johnson Syndrome - D Karunaratne; R Khatri (Nepal Journal of Dermatology, Venereology & Leprology)
Stevens - Johnson syndrome (SJS) is a severe, episodic, acute mucocutaneous reaction that is most often elicited by drugs and occasionally by infections. We report a case of 29 years old woman who developed Stevens - Johnson syndrome following the ingestion of Nimesulide tablets. Nimesulide is a nonsteroidal anti-inflammatory (NSAID) drug with antipyretic and analgesic properties. To the best of our knowledge there have been no previous reports of SJS induced by the ingestion of Nimesulide in the medical literature. This case highlights the importance of Nimesulide and other NSAIDS as the possible cause of Stevens - Johnson syndrome which needs to be borne in mind by the treating physician in cases of drug reactions.